Pathway insights: exploring profiles and processes of drop-in students in relation to completion rates in second chance education - Van Den Berghe, Lana; De Pauw, Sarah S. W.; Vandevelde, Stijn (Frontiers in Psychology, 2025)
IntroductionObtaining an upper secondary degree is highly esteemed for its economic and societal value. For students dropping out of school who return to education to earning an upper secondary degree (cf. high school—ISCED level 3)—termed “drop-in students” in this study—alternative pathways like “Second Chance Education” (SCE) have emerged. Empirical studies on these programs are limited, hindering theoretical progress and the understanding of drop-in students’ psychological and educational processes. To address this, the study aims to examine the profiles of drop-in students and the processes that may influence course completion rates in SCE. In doing so, it contributes to the growing body of research on SCE by investigating (1) student profiles and (2) the processes potentially affecting completion rates within a large sample of drop-in students.MethodsOn this basis, a novel model was developed, including background variables (demographic, educational, and employment information), individual processes (educational motivation, aspirations, psychological needs, and wellbeing), and environmental processes (supportive relationships and contextual barriers). Conducted in Belgium, this quantitative study surveyed 528 drop-in students (Mage = 25; 58% male).ResultsThe results advance theoretical understanding and offer insights into the profiles of drop-in students and the processes influencing completion rates (i.e., lower completion rates for those students who speak a different home language, experienced grade retention, have lower motivational quality, higher relatedness and competence frustration, and fewer supportive relationships).DiscussionThis study points to implications of reimagining support for students in education, emphasizing the need for a comprehensive approach to address various aspects simultaneously.